Deforestation, arsenic, and the self-organizing jungle in the Terai region of Nepal (Journal of Nepal Geological Society, 2004)
The objectives of this study were (1) to determine whether As contamination of groundwater in the Terai region of Nepal could result from deforestation and (2) to understand the As cycle in terms of the theory of complexity. The hypothesis is that jungle includes a microbial population that sequesters As in immobile form during the dry season and converts As into mobile form during the monsoon season. When jungle is converted into pasture or agricultural land, the new microbial population keeps As in mobile form throughout the year. The hypothesis was tested near Hiraganj (Nawalparasi District) and near Bardibas (Mahottari District). At each site, soil was collected from the A and B horizons along five traverses across jungle and adjacent pasture in February (dry season) and June (beginning of monsoon season). Mobile soil As was measured by extraction with 1 M HCI. At the Hiraganj site, jungle mobile soil As rose from (260 ± 20) µg/kg in February to (350 ± 20) µg/kg in June, while the pasture mobile soil As was (370 ± 30) µg/kg in February and (360 ± 20) µg/kg in June. At the Bardibas site, jungle mobile soil As was (190 ± I0) µg/kg in February and (250± 40) µg/kg in June, while the pasture mobile soil As was (240 ± 20) µg/kg in February and (230 ± I0) µg/kg in June. Variation in mobile soil As could not be explained simply in terms of variation in soil pH or gravitational water content.